1999
DOI: 10.1203/00006450-199906000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Binding Angiogenic Factors (Basic Fibroblast Growth Factor and Vascular Endothelial Growth Factor) in Early Neonatal Life

Abstract: This study investigated whether serum levels of the potent angiogenic factors basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF), which are abundantly produced in utero by the placenta and fetal tissues, change after birth at term, consequent to diminished angiogenic but increased adaptational demands in extrauterine life. Moreover, whether serum levels of the above factors correlate with sex, birth weight, or mode of delivery was also evaluated. One milliliter of blood was dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…A marked increase in plasma VEGF has occurred in term infants postnatally [19]. Similarly, a rapid postnatal increase has been reported in circulatory angiogenin levels during the first postnatal days [20]; moreover, this increase in angiogenin levels has been shown to continue until adulthood [21].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A marked increase in plasma VEGF has occurred in term infants postnatally [19]. Similarly, a rapid postnatal increase has been reported in circulatory angiogenin levels during the first postnatal days [20]; moreover, this increase in angiogenin levels has been shown to continue until adulthood [21].…”
Section: Discussionmentioning
confidence: 85%
“…In what is, to our knowledge, the first study to compare VEGF concentrations between preterm and term fetuses, we discovered correlations between gestational age and both VEGF and angiogenin concentrations in umbilical cord plasma; previously no correlations seem to have been noted between gestational age and pulmonary VEGF levels in preterm infants nor between gestational age and circulatory VEGF levels in term infants [18,19]. A marked increase in plasma VEGF has occurred in term infants postnatally [19].…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, disruption of VEGF Ϸ4 weeks after birth had no effect on mortality and only minor effects on tissue vascularity, suggesting a developmental switch in VEGF-mediated new blood vessel formation. Another group reported that VEGF levels increased dramatically after birth in human neonates (27). These findings suggest that neovascularization in the immediate postnatal period, in contrast to the adult animal, may be sensitive to VEGF.…”
Section: Discussionmentioning
confidence: 88%
“…Newborn serum VEGF levels increase sharply after birth and are higher than adult levels (27). Because VEGF is known to increase circulating BM-EPCs (28), the relative numbers of circulating BM-EPCs may be higher in the newborn period.…”
Section: Discussionmentioning
confidence: 99%
“…Ariadne and colleagues reported that the plasma level of VEGF rose significantly in early neonatal life compared with the levels in umbilical cord blood [21]. Increase of VEGF in the early neonatal period may reflect the physiological development of vessels in the neonatal period [22].…”
Section: Discussionmentioning
confidence: 99%